2013
DOI: 10.4103/0019-5545.105512
|View full text |Cite
|
Sign up to set email alerts
|

A study on professional stress, depression and alcohol use among Indian IT professionals

Abstract: Background:Stress has touched almost all professions posing threat to mental and physical health. India being the Information Technology (IT) hub with lakhs involved as IT Professionals, there is a need to assess prevalence of professional stress, depression and problem alcohol use and understand their association.Objectives:(1) To screen for the prevalence of professional stress, risk for depression and harmful alcohol use among software engineers. (2) To study the association between professional stress, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
3
32
0
2
Order By: Relevance
“…respectively as observed among IT professionals in Chennai by Vimala and Madhavi [21] interval 21.2 to 93.1 (P=0.002) and Darshan, et al [24] found that 43.9% singles, 35.7% married and 60% who were committed but unmarried were at risk of developing depression.…”
Section: Discussionmentioning
confidence: 84%
“…respectively as observed among IT professionals in Chennai by Vimala and Madhavi [21] interval 21.2 to 93.1 (P=0.002) and Darshan, et al [24] found that 43.9% singles, 35.7% married and 60% who were committed but unmarried were at risk of developing depression.…”
Section: Discussionmentioning
confidence: 84%
“…É possível que essa nova realidade contribua para elevada incidência de transtornos mentais e comportamentais e das doenças do sistema osteomuscular e do tecido conjuntivo, todos notadamente influenciados por fatores psicossociais, estresse na atividade funcional e formas de organização dos processos de trabalho 12,24,25,26,27,28,29,30 . Some-se a isso o fato de que o progresso tecnológico intenso interferiu na atividade da empresa e, objetivamente, no trabalho do carteiro.…”
Section: Discussionunclassified
“…• • присуство неких фактора радне средине (бука, прашина, хемикалије, микроклима итд. (13,14) . Међу факторима који су чест и значајан извор стреса на послу могу се издвојити фактори радне околине (опасни или непријатни услови рада: бука, загађење ваздуха, неприлагођени радни услови, прео птерећеност, итд.…”
Section: стрес на раду и извори стреса на радуunclassified